Hey there!
y = -2x + 19
y = x + 7
We gonna solve this system of equation by using the substitution method.
We wanna solve y = -2x + 19 for y
Let start by substitute -2x + 19 for y in y = x + 7
y = x + 7
-2x + 19 = x + 7
Subtract x from both sides
-2x + 19 - x = x + 7 - x
-3x + 19 = 7
Now subtract 19 on both sides
-3x + 19 - 19 = 7 - 19
-3x = -12
Then divide both sides by -3
-3x/-3 = -12/-3
x = 4
We have the value of x. Now we gonna use that same value to find the value for y.
We gonna do that by substitute 4 for x in y = -2x + 19
y = -2x + 19
y = -2(4) + 19
y = -8 + 19
y = 11
Thus,
The answer is: x = 4 and y = 11
Let me know if you have questions about the answer. As always, it is my pleasure to help students like you!
Answer:
the two coefficients are 2/3 and -1/6
the sum of the expressions are =
1
/2
q−r+
−3
/4
Step-by-step explanation:
Multiply 1 4/5 by 5
9/5 * 5/1 = 45/5 = 9 miles
Answer:
If you mean 15,048 ÷ 76, the quotient is 198.
If you mean 76 ÷ 15,048, the answer is 0.00505050505. But I doubt that’s what you mean.